Studying the engineering and physical properties of seeds for some crops and their effect on the properties of feeders in seeders. - حبيب ربيع; التنبي محمد نور الدين (Latakia University Journal -Engineering Sciences Series, 2020)
A proper matching of agricultural machinery with properties of materials forms the essential requirements which lead to best performance of machine. To achieve that goal, availability of data and precision analysis on engineering and physical properties of these materials is required. This forms important and necessary data base for the design, development and structure of agricultural machinery and equipments, control and analysis of machines and determination of efficiency of machines. This research was carried out to study some engineering and physical properties of seeds of common Syrian crops to be used in the design and development of some agricultural machinery and equipments. Results provided the shapes and dimensions of cells of feeding devices for planting seeds of some crops namely, wheat, maize, lentil, pea, chick-pea, kidney bean, broad bean and cotton. In addition a set of empirical equations were established to be used to predict, with reasonable accuracy, the physical properties of crops seeds based on measurement of any of three dimensions (length, width and thickness).